Phase 2 of CATALISE: a multinational and multidisciplinary Delphi consensus study of problems with language development: Terminology - Bishop, D; Snowling, M; Thompson, P; Greenhalgh, T; CATALISE-2 consortium (Wiley, 2017)
This record also includes a French translation of the article.